INSTITUSIONALISASI PARTAI POLITK: STUDI KASUS HEGEMONI PAN DI SULAWESI TENGGARA - Eka Suaib; La Husen Zuada; I Wayan Gde Suacana (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2016)
Focus articles namely institusionalizationpolitical party with case study PAN Southeast Sulawesi.Although nationally PAN occupy a board the middle , but in Southeast Sulawesi occupy the top.Hegemony PANSoutheast Sulawesi seen in the seats at an election 2004,2009, 2014 and the fight for regional head election (Pilkada) carried out the period 2010-2013.It was just that , hegemony PAN did not come from institusionalization politicalparty but based on the power of personal. The beginning formation of the process ofinstitusionalization in line with onthe track , but in the following development this process is not workingbecause of the emergence of a strong personalize them in the body of internal pan namely Nur Alam.The figure of this is so strong so as to create patronage both in internal party and exit.To create a voter loyalty, then introduced the program BAHTERAMAS which included the types of programmatic goods.As a result, PAN experienced a dilemma because the process institusionalization politicalparty did not function as intended and program design is not sustainable. Strengthening personalize them in the body party because institusionalizationof the weak. This situation should anticipated by the party, if the party rely on the strength of figure, when he has no base material and resources strong , but political parties will also weakened.